Issues, challenges, and ways ahead to develop citizen-centric e-Governance in Nepal - Rai, Shyan Kirat (Journal of Management and Development Studies, 2022)
E-Governance is a mechanism to provide services to the citizens through online platform utilizing the tools of Information and Communication Technology (ICT) to ease the service delivery process. It is a technological intervention to enhance the existing working process of the organizations. The traditional working process demands a lot of time and human contacts. In addition, the service seekers need to present some vital documents like citizenship certificate and other relevant documents to receive the services. The E-government systems are online systems that citizens can access from anywhere at their convenience to request for the service. The online systems have to be citizen-centric so that they are attracted to use the systems for requesting government services. In Nepal, citizen-centric e-Governance is still at question due to the traditional governance system, lack of awareness and motivation in political leadership, lack of citizen involvement, dearth of adequate research on technology adoption, existing digital divide, difficulties in change management, insufficient ICT infrastructure, lack of integration in online services, and lack of strategic plan for the IT human resources. Exploring various literatures, lessons learned from previous experiences and existing situation of the government implanting whole-of-a-nation thought in the mind-set of leadership can help minimize these issues and move towards citizen-centric approach in e-Governance design, development and implementation.